Reproductive biology and seasonal dynamics of the peanut worm Antillesoma antillarum (Phascolosomatiformes: Phascolosomatidae) in Toronipa, Southeast Sulawesi, Indonesia - BAHTIAR BAHTIAR; MUHAMMAD NUR FINDRA; AGUS KURNIA; YNGWY EZRA JIWANI (Society for Indonesian Biodiversity, 2025)
Abstract. Bahtiar, Findra MN, Kurnia MA, Jiwani YE. 2025. Reproductive biology and seasonal dynamics of the peanut worm Antillesoma antillarum (Phascolosomatiformes: Phascolosomatidae) in Toronipa, Southeast Sulawesi, Indonesia. Biodiversitas 26: 6458-6468. Antillesoma antillarum, commonly known as the peanut worm, is a benthic invertebrate with important ecological and economic roles in coastal ecosystems. However, the lack of reproductive biological data may threaten its sustainability under increasing harvesting pressure. This study examined seasonal variations in reproductive traits sex ratio, gonadal Maturity Level (GML), Gonadosomatic Index (GSI), fecundity, and size at first maturity (Lm₅₀) based on 688 specimens collected over 11 months from the Toronipa Coast, Southeast Sulawesi, Indonesia. Females slightly outnumbered males (374 vs. 314), but the sex ratio did not significantly differ from 1:1 (χ²: 5.23, p>0.05). Gonadal development followed four distinct maturity stages, with peak reproductive activity observed in November-December, when over 60% of individuals reached stages III-IV. GSI values followed a similar pattern, peaking at 6.42% before sharply declining post-spawning. The first maturity size (Lm₅₀) was estimated at 8.0 cm (R²: 0.9946), and fecundity ranged from 920 to 4,500 eggs, with the highest egg counts in individuals measuring 8.0-8.5 cm in length. Although seawater temperature remained stable (30-33°C), allowing gonadal development to occur year-round, elevated sediment organic matter (>3.5%) negatively affected GSI (R: -0.1196), suggesting that sediment quality does not directly influence gonadal development. These findings provide critical baseline data for reproductive-based management, supporting the implementation of size limits (≥8 cm) and seasonal harvest closures to ensure the sustainability of A. antillarum populations in tropical intertidal zones.